Rare Case of Ulnar-Mammary-Like Syndrome With Left Ventricular Tachycardia and Lack of TBX3 Mutation - Zlotina, Anna; Kiselev, Artem; Sergushichev, Alexey; Parmon, Elena; Kostareva, Anna (Frontiers in Genetics, 2018)
"Heart-hand" type syndromes represent a group of rare congenital conditions that combine cardiac pathology (structural defect or arrhythmic disorder) and limb abnormality. Significant clinical variability and genetic heterogeneity typical for such syndromes complicate correct diagnosis, prognosis and appropriate genetic counseling of the affected families. By now, only single genes have been unambiguously determined as a genetic cause of heart-hand syndromes and phenotypically similar conditions. In the present study, we report on a 25-year-old Russian female patient with a clinical picture resembling ulnar-mammary syndrome (UMS). Principal clinical manifestations included heart septal fibrosis and non-sustained left ventricular tachycardia combined with fifth finger camptodactyly, hypoplastic breast, abnormal teeth and mental retardation. Target Sanger sequencing and array-based comparative genome hybridization confirmed the lack of pathogenic mutations and large-scale deletions in TBX3 (12q24.21), the only gene known to be associated with UMS cases to date. Based on the results of whole-exome sequencing, 14 potential candidate variants were identified. Among them, a novel missense variant in SYNM gene (exon 1, c.173C>T, p.A58V), encoding intermediate filament protein synemin was characterized. Until the present, no association between SYNM mutations and congenital clinical syndromes has been reported. At the same time, taking into account synemin tissue-specific expression profiles and available data on abnormal knock-out mice phenotypes, we propose SYNM as a candidate gene contributing to the UMS-like phenotype. Further comprehensive functional studies are required to evaluate possible involvement of SYNM in genesis of complex heart-limb pathology.